(untitled) (Philippines, 1994)
Horticulture is the art, science, technology, and business of growing and utilizing garden and plantation crop. It is an art, as creativity is applied in using plants to enhance the beauty, economic value, and utility of homes, shops, public buildings and parks. It is a science in that there is an orderly array of basic facts that explain and direct crop performance. It is a technology, because systematic practices and operations are essential with to successful crop production. And it is a business in that it is concerned with profit, this aspect of horticulture is sometimes known as commercial horticulture.
Keywords: Horticulture,Rau quả